Die Bevölkerung Algeriens - Suter, Karl (ERDKUNDE, 1961)
In Algeria two major regions may be distinguished: the Tell with Mediterranean climate, arable farming and sedentary life, and the high plateau steppe with continental climate, pastoral economy and nomadic life. Since time immemorial the country has been inhabited by various Berber groups such as the Kabyles of Kabylia, the Chaouias of the Aures Mts. and the Mozabites in the north Algerian Sahara (Mzab). In these out of the way areas they were able to preserve their language, their customs and way of life, their social organisation (clans) and their peculiar legal and social institutions, and to outlast the various invasions which North Africa suffered over the centuries. The most lasting of these invasions was that by the Arabs, largely the advance of a number of Bedouin tribes in the 11th century. Many Berber groups became Arabicized by acceptance of the language, religion and mental attitudes of the Bedouins. Although it is impossible to analyse by means of physical anthropology the proportion of the present population which is of Berber extraction, it may be estimated that ca. 80% of the Algerians are of such origin. The Islam, the religion of both the Arab and the Berber inhabitants, exerts a powerful influence over their entire life, in particular in its social, legal and economic spheres. Besides the 8.5 million Mohammedans, the 130,000 Jews form merely a small minority which is however economically very active. The European population, amounting to over a million, is mainly composed of French and Spanish immigrants and their descendants born in the country. Algeria is thus inhabited by very dissimilar population groups; the economic, cultural, religious, social and sociological contrasts cause tensions. The ethnic disunion is the reason why the country has never been an independent state of its own, and has lacked a national consciousness. When in 1830 the French came into the country they merely replaced the occupation by the Turks. France has accomplished an imposing civilisatory task but it has not succeeded in providing for the quickly growing indigenous population sufficient means to earn a decent livelihood. Discontent grew alarmingly. The panacea is now sought in intensification of industrialisation especially since the discovery of oil and natural gas in the Sahara as new sources of energy. Urbanisation proceeds at a quick pace and new social strata are emerging. The Algerian people have a right to take their destiny into their own hands but, regardless which way they may decide, Algeria as a state of the western Mediterranean needs economic links with the West, particularly with France.